Phytochemical Screening, Biochemical Composition, and Antibacterial Activity of Leaves and Stems of Lavender from Al‑Jabal Al‑Akhder Region, Libya - Hamad Hasan; Fatimah Abdulsayid; Boodor Alshareef; Salem Mahmoud; Zuhir Ikrim; Salha Sergewa (AlQalam Journal of Medical and Applied Sciences, 2026)
Lavender is a common and popular aromatic Mediterranean herb that belongs to the Lamiaceae family. It is a species largely used in traditional medicine for its biological properties allotted primarily to polyphenols. The leaves and stems of the Lavender plant were collected from Ain-Mara and Ras-Elhelal in the Al-Gabel Al –Kadar region during the spring season of 2024. The Phytochemical screening and antibacterial activity were applied to the extracts of the leaves and stems of Lavandula plants. The results showed that the phytochemical screening of aqueous and methanolic extracts of the studied samples showed that some phytochemicals are present, while others are absent, like anthraquinone, which is absent in aqueous and methanolic extracts in leaves and stems of the lavender plant. The total carbohydrate, total amino acids, total proteins, and total phenols contents (ppm) were higher in leaves than in stems of lavender plant extracts. The anti-bacterial activity was carried out on two different species (Staphylococcus and E. coli). There are small variations in the inhibition zones of the studied lavender plant. A high effect was observed for high concentrations (100 and 75 %) of E. coli and Staphylococcus of lavender leaf extract only.